The Effect of Physical Activities on Biological Age Parameters of Females from 17 to 18 Years Old - Thuc, Dao Chanh (Journal of Sports Research, 2018)
The effect of weekly physical activity on biological age (BA) parameters, we have conducted a study 215 females from 17 to 18 years old who were divided into the experimental (EG, n=105) and control (CG, n=110) groups. It was established that if at the end of the experiment the BA parameters of the females CG weren’t a significantly different from the average data (p>0.05), then there was a statistically significant decrease in the BA parameters of the females EG. This was confirmed by statistical probability (p<0.01), which suggests the dependence of biological age parameters on the extent of weekly physical activity.